Needs Around Dialysis Treatment from Different Perspectives (NADIP): Results of the Exploratory German Multicenter Survey - Patrick Biggar; Dennis Hidde; Markus Ketteler (Karger Publishers, 2019)
Background/Aims: In 2015, approximately 70,000 patients with end-stage renal disease were treated chronically with dialysis in Germany. However, there is only sparse information regarding subjective appreciation of the different aspects of extracorporeal renal replacement therapies. This study was performed to gain insight into the needs and appreciation of services in dialysis centers in Germany including the views not only of the patients but also of the caregivers, physicians, and nurses. Methods: A cross-sectional written voluntary questionnaire survey based on the international RAND Kidney Disease Quality of Life Short Form (version 1.3) comprising 510 adult dialysis patients, 274 caregivers, 29 physicians, and 60 nurses in 30 dialysis centers across Germany. Results: Although patients were mostly satisfied with present treatment options, room for improvement exists. Patients were less critical of services than doctors and nurses. Factors such as trustworthy contact with staff at the centers as well as information exchange with other patients and among caregivers play a significant role in the patients' perception of a high-quality dialysis treatment facility. Therefore, continued cost saving, in particular regarding personnel, may subjectively counteract the objective technical improvements of dialysis. Conclusions: High-quality technical standards are essential for successful dialysis therapy; however, additionally, we recommend an array of communicative and social tools employed by all stakeholders to convey and exchange information and also support subjective well-being. This survey represents one of the largest evaluations to date. The data are also of potential international relevance for non-German health management systems.